THE EFFECT OF FINANCIAL LITERACY AND SELF-CONTROL ON THE CONSUMER BEHAVIOR OF SHOPEE PAYLATER USERS AMONG STUDENTS OF THE MANAGEMENT STUDY PROGRAM, CLASS 2022-2025 AT UNIVERSITAS NEGERI MAKASSAR - Widya Putri Clarissa Wahid; Nurman Nurman; Andi Mustika Amin; Anwar Ramli; Abdul Rahman (Jurnal Manajemen, 2026)
Abstract: This study aims to determine and analyze the influence of financial literacy and self-control on the consumer behavior of Shopee PayLater users in the Management Study Program, intake 2022-2025, at Universitas Negeri Makassar. This study used a quantitative approach with a survey method. The variables in this study consisted of financial literacy (X₁) and self-control (X₂) as an independent variable and consumer behavior (Y) as a dependent variable.The results of this study indicate that: (1) Financial literacy partially has a negative and significant effect on the consumer behavior of Shopee PayLater user students in the Management Study Program at Universitas Negeri Makassar. (2) Self-control partially has a negative and significant effect on the consumer behavior of Shopee PayLater user students in the Management Study Program at Universitas Negeri Makassar. (3) Financial literacy and self-control simultaneously have a significant effect on the consumer behavior of Shopee PayLater user students Keywords: Financial Literacy, Self-Control, Consumptive Behavior, Shopee PayLaterKeywords: Financial Literacy, Self-Control, Consumptive Behavior, Shopee PayLater